Modelling the antecedents of customer behavioural intention in the childcare services industry. - Nik Syuhailah Nik Hussin (2021)
The increasing participation of women in the labour force comes in tandem with an escalating cost of living that demands dual incomes for families. This has inadvertently increased the demand for childcare services, to support the family institution. As a result, stiff competition has been noted amongst childcare service providers in retaining their existing customers. Nevertheless, experience of poor quality service has raised multiple issues that seem to affect the behavioural intention of parents as customers of childcare services. Hence, this study attempts to develop a model that explains the antecedents of customer behavioural intention in the Malaysian childcare service industry, and tests it empirically. The literature lists four antecedents of customer behavioural intention, namely: i) service quality; ii) perceived trust; iii) emotional satisfaction; and iv) perceived risk towards childcare service providers. Based on the Stimulus-Organism-Response Theory (SOR) and Expectancy Confirmation Theory (ECT), a mediational model is proposed in this study which links service quality with customer behavioural intention via perceived trust, emotional satisfaction, and perceived risk. By employing a purposive sampling method, 750 questionnaires were administered to the respondents at selected childcare centres. A total of 554 questionnaires were returned - representing a 73.8 percent response rate. However the usable questionnaires for analysis were 364. The data was analysed using SPSS 23.0 and SmartPLS SEM 3.2.9. Service quality was conceptualised as a second- order construct arrived at through a reflective-reflective model using a two-stage approach.